A Comparison of Central Composite Design and Taguchi Method for Optimizing Fenton Process - Anam Asghar; Abdul Aziz Abdul Raman; Wan Mohd Ashri Wan Daud (The Scientific World Journal)
In the present study, a comparison of central composite design (CCD) and Taguchi method was established for Fenton oxidation. Dyeini, Dye : Fe+2, H2O2 : Fe+2, and pH were identified control variables while COD and decolorization efficiency were selected responses. L9 orthogonal array and face-centered CCD were used for the experimental design. Maximum 99% decolorization and 80% COD removal efficiency were obtained under optimum conditions. R squared values of 0.97 and 0.95 for CCD and Taguchi method, respectively, indicate that both models are statistically significant and are in well agreement with each other. Furthermore, Prob > F less than 0.0500 and ANOVA results indicate the good fitting of selected model with experimental results. Nevertheless, possibility of ranking of input variables in terms of percent contribution to the response value has made Taguchi method a suitable approach for scrutinizing the operating parameters. For present case, pH with percent contribution of 87.62% and 66.2% was ranked as the most contributing and significant factor. This finding of Taguchi method was also verified by 3D contour plots of CCD. Therefore, from this comparative study, it is concluded that Taguchi method with 9 experimental runs and simple interaction plots is a suitable alternative to CCD for several chemical engineering applications.